The Effects of Various Parameters on Cr (VI) Adsorption by Raw Rice Husk - P, Subramaniam; N.A, Khan; Ibrahim, Shaliza (Malaysian Journal of Science, 2006)
The effects of pH, contact time and adsorbent concentration on the adsorption of Cr (VI) onto raw rice husk have been investigated. The parameters - raw rice husk (RRW) particle size which was in the range of 450-600 Ã‚Âµm, concentration from 10g/1 to 70g/1, contact time 0.5 to 2.0 hours, and pH 1-8 were tested using 50mg/1 solutions of Cr (VI). The maximum removal efficiency was 66.6% for RRW concentration of 70g/1, at pH 2 and 2 hours contact time. In terms of adsorption capacity, the 10g/1 adsorbent concentration gave the highest reading of 2.2 mg/g for a pH of 2 and 2 hours contact time.